2013
DOI: 10.1007/s00392-013-0545-6
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic involvement in idiopathic premature ventricular contractions

Abstract: HR dependency reflected autonomic modulation of idiopathic PVCs. F-PVC and S-PVC might be facilitated by sympathetic activation and vagal activation, respectively. HR dependency and the related autonomic mechanisms should be considered when treating idiopathic PVCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 25 publications
2
38
1
Order By: Relevance
“…The difference in the degree of night-time PVC suppression between the P-PVC and NP-PVC groups may have contributed to a significant mean night-time HR reduction in the P-PVC group compared to the NP-PVC group. There was no significant difference observed in the change in the mean day-time HR (p = 0.28) from baseline, however, a trend was observed in that the degree of the change in the mean day-time HR was larger in the [8]. In this study, the bisoprolol patch did not change the PVC count significantly (p = 0.080) in patients with negative HR-dependent PVCs.…”
Section: Efficacy Of the Bisoprolol Patch On Frequent Pvcs In Patientcontrasting
confidence: 61%
See 3 more Smart Citations
“…The difference in the degree of night-time PVC suppression between the P-PVC and NP-PVC groups may have contributed to a significant mean night-time HR reduction in the P-PVC group compared to the NP-PVC group. There was no significant difference observed in the change in the mean day-time HR (p = 0.28) from baseline, however, a trend was observed in that the degree of the change in the mean day-time HR was larger in the [8]. In this study, the bisoprolol patch did not change the PVC count significantly (p = 0.080) in patients with negative HR-dependent PVCs.…”
Section: Efficacy Of the Bisoprolol Patch On Frequent Pvcs In Patientcontrasting
confidence: 61%
“…PVCs were divided into two types based on their HR dependency, which was evaluated by the relationships between the hourly PVC density and hourly mean HR measured by 24-hour Holter ECGs. The methods were fundamentally the same as those reported by He et al [8]. Then their relationship was analyzed by a Pearson's correlation.…”
Section: Relationship Between the Pvc Density And Hrmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of VPCs has a diurnal pattern, with fewer VPCs occurring during sleep and more during waking hours. 24 He et al 25 demonstrated the heart rate dependency of idiopathic VPCs by comparing HRV parameters and VPC density. previous HRV studies showed that PM2.5 exposures affect the autonomic system.…”
Section: Diurnal Effect Of Pm25 On Vpcsmentioning
confidence: 99%